Tailoring Dzyaloshinskii–Moriya Interaction and Spin‐Hall Topological Hall Effect in Insulating Magnetic Oxides by Interface Engineering - Zedong Xu; Yuanmin Zhu; Yuming Wang; Xiaowen Li; Qi Liu; Kai Chen; Junling Wang; Yong Jiang; Lang Chen (Advanced Science)
Abstract Chiral spin textures, as exotic phases in magnetic materials, hold immense promise for revolutionizing logic, and memory applications. Recently, chiral spin textures have been observed in centrosymmetric magnetic insulators (FMI), due to an interfacial Dzyaloshinskii–Moriya interaction (iDMI). However, the source and origin of this iDMI remain enigmatic in magnetic insulator systems. Here, the source and origin of the iDMI in Pt/Y3Fe5O12 (YIG)/substrate structures are deeply delved by examining the spin‐Hall topological Hall effect (SH‐THE), an indication of chiral spin textures formed due to an iDMI. Through carefully modifying the interfacial chemical composition of Pt/YIG/substrate with a nonmagnetic Al3+ doping, the obvious dependence of SH‐THE on the interfacial chemical composition for both the heavy metal (HM)/FMI and FMI/substrate interfaces is observed. The results reveal that both interfaces contribute to the strength of the iDMI, and the iDMI arises due to strong spin−orbit coupling and inversion symmetry breaking at both interfaces in HM/FMI/substrate. Importantly, it is shown that nonmagnetic substitution and interface engineering can significantly tune the SH‐THE and iDMI in ferrimagnetic iron garnets. The approach offers a viable route to tailor the iDMI and associated chiral spin textures in low‐damping insulating magnetic oxides, thus advancing the field of spintronics.